2021
DOI: 10.1007/s13402-020-00500-0
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulated exosomal microRNA-148b-3p in cancer associated fibroblasts enhance chemosensitivity of bladder cancer cells by downregulating the Wnt/β-catenin pathway and upregulating PTEN

Abstract: Objective Exosomes derived from cancer-associated fibroblasts (CAFs) are known as important drivers of tumor progression. Previously, microRNA (miR)-148b-3p has been found to be upregulated in bladder cancers as well as in body fluids (blood, urine) of bladder cancer patients. Here, we aimed to explore the role of CAF-derived exosome miR-148b-3p in bladder cancer progression and chemosensitivity. Methods Transwell, MTT, flow cytometry and colony formation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(72 citation statements)
references
References 39 publications
1
71
0
Order By: Relevance
“…Increasing evidence has revealed their clinicopathological significance in predicting outcomes and therapeutic efficacy ( Greten and Grivennikov, 2019 ; Vitale et al, 2019 ; Suzuki et al, 2021 ). TAMs and CAFs in TME always accelerate tumor progression ( Akins et al, 2020 ; Liu et al, 2021 ; Shan et al, 2021 ). Our results revealed that CCDC137 have close relationships with TAMs and CAFs infiltration in most tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence has revealed their clinicopathological significance in predicting outcomes and therapeutic efficacy ( Greten and Grivennikov, 2019 ; Vitale et al, 2019 ; Suzuki et al, 2021 ). TAMs and CAFs in TME always accelerate tumor progression ( Akins et al, 2020 ; Liu et al, 2021 ; Shan et al, 2021 ). Our results revealed that CCDC137 have close relationships with TAMs and CAFs infiltration in most tumor types.…”
Section: Discussionmentioning
confidence: 99%
“…Some exosomal miRNAs have been identified to initiate or prevent EMT processes in BCa through the Wnt/β-catenin signaling pathway. Exosomal miR-148b-3p is secreted by cancer-associated fibroblasts and is transmitted into BCa cells and acts as a tumor promotor to trigger EMT initiation by interacting with the PTEN gene ( 64 ). Unlike miR-148b-3p, Li et al.…”
Section: The Biological Roles Of Exosome-derived Ncrnas In Bcamentioning
confidence: 99%
“…By examining the sensitivity of BCa cells to Paclitaxel (PTX) and doxorubicin (DOX), Shan et al. demonstrated that after treatment, exosomes derived from cancer-associated fibroblasts, T24 and 5367 cells, showed lower levels of apoptosis, indicating exosomal miR-148b-3p contributed to the reduction in chemosensitivity ( 64 ). Liang et al.…”
Section: The Biological Roles Of Exosome-derived Ncrnas In Bcamentioning
confidence: 99%
“…Several studies have demonstrated that exosomal activity might be involved in chemo-resistance. In EMT, Shan et al indicated that downregulation of exosomal miR-148b-3p may offer opportunities in the treatment of bladder cancer by increasing chemosensitivity via inhibition of the Wnt/β-catenin pathway and promoting expression of PTEN [95]. In addition to it, Liu et al reported that exosome-transmitted miR-128-3p increased chemosensitivity of oxaliplatin-resistant colorectal cancer by suppressing epithelial-mesenchymal transition and inducing drug accumulation in cancer cells [96].…”
Section: Exosomes In Chemotherapy and Other Therapymentioning
confidence: 99%